Mutu Fisik dan Stabilitas Sediaan Body Scrub Ekstrak Buah Salak Pondoh (Salacca edulis Reinw.) dengan Emulgator Asam Stearat dan Trietanolamin - Indri Kusuma Dewi; Pramita Yuli Pratiwi; Alvita Defayanti (LPPMKI - AKAFARMA AKFAR PIM, 2023)
Salak pondoh fruit contains flavonoids that can be used to ward off free radicals. The content of the salak fruit can be used as a body scrub that functions to remove dead skin cells. The purpose of this research was to ascertain how storage time affected the physical stability of body scrub formulations. This study use an experimental with a single group design. The amount of salak pondoh fruit extract used in body scrubs is 0,1%. Physical quality testing carried out includes organoleptics, homogeneity, dispersality, pH, viscosity, and emulsion type, while for physical stability testing, the cycling test method is used, namely the storage method in refrigerators with a temperature of 4ÂºC and storage in an oven with a temperature of 40ÂºC for 6 cycles or 12 days. Based on the results of the physical quality test, the body scrub is white, semi-solid, characteristic aromatic smell, homogeneous, has a pH value of 6,00, a dispersion power of 4.71 cm, a viscosity of 9095 cps, and is an emulsion type M/A. Physical stability test results are qualified on all tests such as organoleptic, homogeneity, pH, emulsion type, viscosity, and dispersion. The analysis with a paired sample t-test revealed a value of >0.05 for the dispersion, pH, and viscosity tests. The study's result is that body scrub preparations pass testing requirements and retain their stability in storage.Â